Extending the Capabilities of Molecular Force Sensors via DNA Nanotechnology - Beltrán, Susana M. (Crit Rev Biomed Eng, 2020)
At the nanoscale, pushing, pulling, and shearing forces drive biochemical processes in development and remodeling as well as in wound healing and disease progression. Research in the field of mechanobiology investigates not only how these loads affect biochemical signaling pathways but also how signaling pathways respond to local loading by triggering mechanical changes such as regional stiffening of a tissue. This feedback between mechanical and biochemical signaling is increasingly recognized as fundamental in embryonic development, tissue morphogenesis, cell signaling, and disease pathogenesis. Historically, the interdisciplinary field of mechanobiology has been driven by the development of technologies for measuring and manipulating cellular and molecular forces, with each new tool enabling vast new lines of inquiry. In this review, we discuss recent advances in the manufacturing and capabilities of molecular-scale force and strain sensors. We also demonstrate how DNA nanotechnology has been critical to the enhancement of existing techniques and to the development of unique capabilities for future mechanosensor assembly. DNA is a responsive and programmable building material for sensor fabrication. It enables the systematic interrogation of molecular biomechanics with forces at the 1- to 200-pN scale that are needed to elucidate the fundamental means by which cells and proteins transduce mechanical signals.